C-Terminal Peptide Modifications Reveal Direct and Indirect Roles of Hedgehog Morphogen Cholesteroylation - Manikowski, Dominique; Kastl, Philipp; Schürmann, Sabine; Ehring, Kristina; Steffes, Georg; Jakobs, Petra; Grobe, Kay (Frontiers in Cell and Developmental Biology, 2021)
Hedgehog (Hh) morphogens are involved in embryonic development, stem cell biology and, if misregulated, can contribute to cancer. One important posttranslational modification with profound impact on Hh biofunction is its C-terminal Hh cholesteroylation during biosynthesis. The current hypothesis is that the cholesterol moiety is a decisive factor in Hh association with the outer plasma membrane leaflet of producing cells, cell-surface Hh multimerization, its transport and signaling. Yet, it is not decided whether the cholesterol moiety is directly involved in all of these processes, because their functional interdependency raises the alternative possibility that the cholesterol initiates early processes directly, and that these processes can then steer later stages of Hh signaling independent of the lipid. We generated variants of the C-terminal Hh peptide and observed that these cholesteroylated peptides variably impaired several posttranslational processes in producing cells and Hh biofunction in Drosophila melanogaster eye and wing development. We also found that substantial Hh amounts separated from their cholesteroylated peptide tags in vitro and in vivo, and that tagged and untagged Hh variants lacking their C-cholesterol moieties remained bioactive. Our approach thus confirms that Hh cholesteroylation is essential during early steps of Hh production and maturation, but also suggests that it is dispensable for Hh signal reception at receiving cells.